Transumbilical Multiport Laparoscopic Nephroureterectomy for Congenital Renal Dysplasia in Children: Midterm Follow-Up from a Single Institution - Mei, Hong; Qi, Teng; Li, Shuai; Pu, Jiarui; Cao, Guoqing; Tang, Shaotao; Zheng, liduan; Tong, Qiangsong (Frontiers in Pediatrics, 2013)
OBJECTIVE: To assess the clinical utility and efficiency of transumbilical multiport laparoscopic nephroureterectomy (TMLN) for the treatment of congenital renal dysplasia in children by analyzing consecutive cases from a single institution. METHODS: Sixteen children underwent TMLN procedure due to dysplastic kidney between January 2010 and December 2011. The surgery was transperitoneally performed through three transumbilical incisions for two 5-mm and one 3-mm ports, which duplicated the standard laparoscopic steps with the usual laparoscopic instruments. Demographic, perioperative, and follow-up data were analyzed. RESULTS: TMLN was performed in all patients, without additional ports or conversion to open surgery. The mean operation time was 108.4 minutes (range 90–125), and the blood loss was minimal. There were no severe intraoperative or postoperative complications. The postoperative recovery was uneventful in all patients. No urinary incontinence or umbilical hernias occurred. The cosmetic result was excellent as the incision scar was hidden inside the belly button. CONCLUSION: TMLN is a safe and efficient procedure for the management of congenital renal dysplasia in children with good cosmesis. Future randomized studies with a larger number of cases and a longer follow-up are warranted to elucidate the benefits and limitations of TMLN in children.